To simplify the expression \( 10(7p + 6) - 5(5p + 4) \), we will distribute the numbers outside the parentheses:
-
Distribute \( 10 \) into \( (7p + 6) \): \[ 10(7p) + 10(6) = 70p + 60 \]
-
Distribute \( -5 \) into \( (5p + 4) \): \[ -5(5p) - 5(4) = -25p - 20 \]
Now, we can combine these results: \[ 70p + 60 - 25p - 20 \]
Next, combine like terms:
- For the \( p \) terms: \( 70p - 25p = 45p \)
- For the constant terms: \( 60 - 20 = 40 \)
Putting it all together, we have: \[ 45p + 40 \]
Thus, the simplified expression is: \[ \boxed{45p + 40} \]